In vitro Antioxidant and anti-inflammatory properties of selected Moroccan medicinal plants - Eimad dine Tariq BOUHLALI, Khalid SELLAM, Mohamed BAMMOU, Chakib ALEM, Younes FILALIZEHZOUTI (Journal of Applied Pharmaceutical Science, 2016)
The aim of the present study was to examine the antioxidant and anti-inflammatory activities of three Moroccan ethno medicinally important plants. The antioxidant activity was performed using β-Carotene bleaching assay, DPPH, ABTS and Ferric reducing assays. In vitro anti-inflammatory assays was also studied through the evaluation of membrane stabilization potential and inhibition of protein denaturation. Results revealed that Lawsonia inermis L leaves extract had significantly higher phenolics-content (5.23 g GAE/100g DW) and exhibited the highest antioxidant activity based on DPPH (IC50 = 18.26 µg/mL). The highest flavonoids content was found in Rosa damascena L flower (3.97 RE/100g DW) which shows the highest antioxidant activity based on ABTS (30.39 mmol TE/100g DW), FRAP (38.54 mmol TE/100gDW) and β-Carotene bleaching assay (IC50 = 56.33 µg/mL). Concerning the anti-inflammatory potency, the highest membrane stabilization effect was found in Rosa damascena L flower (IC50 = 125.02 µg/mL) and the highest anti-denaturation of protein effect was found in Lawsonia inermis L leaves extract (IC50 = 103.21 µg/mL). Consequently, to conclude flavonoids and related phenolics present in studied plant materials may possibly be responsible for the important anti-inflammatory and antioxidant activities.
Keywords: Cuminum cyminum, Lawsonia inermis L, Rosa damascena, antioxidant, anti-inflammatory.